2020
DOI: 10.1111/bjhp.12461
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative examination of affect and ideology within mass media interventions to increase HIV testing with gay men garnered from a systematic review

Abstract: Objectives. Increasing appropriate HIV testing among men who have sex with men (MSM) is crucial to HIV prevention. Mass media interventions are effective in promoting testing, but to date, there has been little examination of their active content. Design. We conducted a qualitative analysis of intervention materials (n = 69) derived from a systematic review of mass media interventions designed to improve testing with MSM. Methods. Visual data were analysed for their affective and ideological content using a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…Our results are in line and are supported by studies indicating that the gay male subculture places great importance on physical appearance, which can lead to a perceived gap between their actual body image and their desired body shape [55]. This gay subculture often promotes the idea that self-worth is tied to a specific aesthetic [56]. Research suggests that gay men base their worth on physical appearance more than heterosexual people [57].…”
Section: Discussionsupporting
confidence: 89%
“…Our results are in line and are supported by studies indicating that the gay male subculture places great importance on physical appearance, which can lead to a perceived gap between their actual body image and their desired body shape [55]. This gay subculture often promotes the idea that self-worth is tied to a specific aesthetic [56]. Research suggests that gay men base their worth on physical appearance more than heterosexual people [57].…”
Section: Discussionsupporting
confidence: 89%
“…As previously stated, the current findings suggest that none of the interventions involved in the study explicitly attempted to address fear of a positive HIV test result, which is surprising given previous evidence suggesting that fear of the result may result in avoidance of testing ( Deblonde et al, 2010 ; Flowers et al, 2013a ; Lui et al, 2018 ). Whilst the current findings do consider the overall tone of the content, a more detailed discussion of affect within these interventions can be found in Langdridge et al (2020) .…”
Section: Discussionmentioning
confidence: 99%
“…The current paper is part of a series of papers presenting findings from a systematic review exploring evidence related to mass media and communication interventions to increase HIV testing among GBMSM. More detailed analysis relating to intervention effectiveness (McDaid et al, 2019), the active content of interventions (Flowers et al, 2019) and affect used within interventions (Langdridge et al, 2020) can be found elsewhere. The current analyses employed rigorous data extraction tools to attempt to identify the common social marketing principles and visual design elements associated with effectiveness across a range of HIV testing campaigns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation